Pengaruh edukasi Range of Motion (ROM) pasif terhadap pengetahuan sikap dan keterampilan keluarga dalam merawat pasien stroke - Marwanti Marwanti; Fitriana Noorkhayati; Sri Rahayuningsih (Health Sciences and Pharmacy Journal, 2021)
Stroke is the highest cause of disability. Stroke patients with paralysis need to do the ROM exercise regularly. Families of stroke patients need an enough knowledge in ordet to do the ROM exercise at home. The purpose of the study is to determine the effect of passive ROM education on families’ knowledge, attitudes and skills in stroke patients at the Klaten Islamic Hospital. This research was a quantitative type with a research design using a quasi-experiment with a pretest-posttest design with a control group. The population in this study were all stroke patients at Klaten Islamic Hospital with an average of 42 patients per month. The sampling technique used was total sampling. The samples were grouped, a total of 21 research respondents were included in the intervention group and there were 21 samples in the control group. The data research instrument used questionnaires and observation sheets to measure and observe the knowledge, attitudes and skills of the family in performing passive ROM on patients. Data analysis used Wilcoxon and Mann Whitney test. The results showed an increase in family knowledge, attitudes and skills about ROM both in the intervention group and the control group. The category of improvement towards the good category mostly occurred in the intervention group. In the intervention group, the results of the assessment showed that the majority of respondents with poor knowledge (71.4%) changed to be good (100%). The attitude of the respondents also increased, from the majority (72.6%) to be good (90.5%). And also on the skill variable, from the majority was less (81%) to be good (100%). The results of the different test showed that there was an effect of passive ROM education on knowledge, attitudes and skills with  p value of 0.000. The conclusion obtained shows that there is an effect of passive ROM education on the knowledge, attitudes and skills of stroke patients' families in both the control and intervention groups.